2015
DOI: 10.1039/c4tb01839g
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in thrombosis and bacterial adhesion with 7 day implantation of S-nitroso-N-acetylpenicillamine (SNAP)-doped Elast-eon E2As catheters in sheep

Abstract: Thrombosis and infection are two common problems associated with blood-contacting medical devices such as catheters. Nitric oxide (NO) is known to be a potent antimicrobial agent as well as an inhibitor of platelet activation and adhesion. Healthy endothelial cells that line the inner walls of all blood vessels exhibit a NO flux of 0.5~4×10 −10 mol cm −2 min −1 that helps prevent thrombosis. Materials with a NO flux that is equivalent to this level are expected to exhibit similar anti-thrombotic properties. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
113
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 47 publications
5
113
1
Order By: Relevance
“…[11, 23] One of the prime objectives in developing NOrel materials is to control as well as prolong the NO-release from these devices. Increasing the lifetime of these materials is generally done through increasing the amount of NO donor that is incorporated in the host material.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[11, 23] One of the prime objectives in developing NOrel materials is to control as well as prolong the NO-release from these devices. Increasing the lifetime of these materials is generally done through increasing the amount of NO donor that is incorporated in the host material.…”
Section: Resultsmentioning
confidence: 99%
“…[23] Longer terms studies have been reported recently of SNAP-E2As catheters, and showed reduce bacterial adhesion and thrombus formation for 7 days in sheep. [11] As evident from the previous studies described above, SNAP-doped E2As possesses great potential for biomedical applications. While NO-releasing polymers have been shown to give excellent results in research settings, antibacterial activity and prevention of thrombus formation are not the only properties to consider when moving towards clinically relevant polymers.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations